BJOG Editor's Choice. (21st April 2016) - Thorp, John
Abstract : Deputy Editor‐in‐Chief, Dr John Thorp, discusses his top articles from this issue in an audio podcast availablehttps://soundcloud.com/bjog/may-editors-choice-2016